Konsep Lingkungan Hidup Dalam Perspektif Al-Qur’an - Budihartono; Hasyim Hadadde; Hamka Ilyas (P@RAD!GMA : Jurnal Kajian Budaya & Media, 2025)
The environment is a vital aspect of human life, deeply interconnected with spiritual values and religious ethics. The Qur’an, as the primary source of Islamic teachings, pays significant attention to the creation, preservation, and balance of the natural world. This article explores the concept of the environment from the Qur’anic perspective using a thematic interpretation (tafsir maudhuu’ii) approach. The findings reveal that the Qur’an not only acknowledges the importance of the environment but also provides normative guidance on how humans should interact with nature responsibly. Key concepts such as khaliifah (stewardship), miizaan (balance), fasaad (corruption), and iḥsaan (excellence in action) form the ethical foundation for environmental management. A deeper understanding of Qur’anic verses on the environment encourages Muslims to internalize ecological values in daily life as a form of worship and social responsibility. This study emphasizes that environmental preservation is not merely an ecological issue but also a theological mandate with eschatological dimensions.